METHODOLOGICAL APPROACHES TO DETERMINING THE PRODUCT RANGE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS FOR THE TREATMENT OF OCCUPATIONAL DISEASES OF THE MUSCULOSKELETAL SYSTEM - Петров, Андрей Георгиевич; Филимонов, Сергей Николаевич; Семенихин, Виктор Андреевич; Хорошилова, Ольга Владимировна; Часовских, Елена Владимировна; Черных, Наталья Степановна (Medicine in Kuzbass, 2021)
The goal is to develop methodological approaches to determining the product range of nonsteroidal anti-inflammatory drugs (NSAIDs) for the treatment of occupational diseases of the musculoskeletal system of coal industry workers.Materials and methods. The object of research in the study of this problem is represented by employees of the coal industry with occupational diseases of the musculoskeletal system (n = 400). The following research methods were used: content analysis, descriptive, information and analytical, marketing, sociological (questionnaires, methods of expert assessments), mathematical and statistical.The research methodology includes key components: selection of a research tool; data collection; database formation; scaling of questionnaire data; statistical data processing; analysis and interpretation of results.Results. A modified methodological approach has been developed to determine the product range of nonsteroidal anti-inflammatory drugs for the treatment of occupational diseases of the musculoskeletal system of coal industry workers. With a sufficient number of different indications for use, NSAIDs have a large number of side effects and limitations, which necessitates mandatory strict control over their appointment, release and use. To evaluate the effectiveness of treatment in a particular patient according to individual monitoring data and use these data to correct treatment and prevention.Conclusion. The performed studies confirm the need for a detailed assessment of the product range of NSAIDs and the impact on the treatment and prevention of occupational diseases of the musculoskeletal system. On its basis, it is possible to more effectively form the necessary medical and pharmacoprophylactic measures in the prevention of occupational diseases of the musculoskeletal system of coal industry workers.
Keywords: marketing research; occupational diseases; assortment of nonsteroidal anti-inflammatory drugs